Pengaruh Struktur Modal, Ukuran Perusahaan, Kepemilikan Manajerial Dan Agency Cost Sebagai Variabel Intervening Terhadap Kinerja Perusahaan (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftardi Bursa Efek Indonesia Tahun 2011-2013) - Ruviah, Khaniv Ni' Matur; , Drs. Muhammad Abdul Aris, M.Si (2015)
Performance of the company is activities and results that can be achieved by the group in realizing the goals, objectives, vision, mission contained in the strategic plan of a company, but the company often conflicts agency. The agency conflict will lead to agency cost which would have a negative impact on the performance of the company. This study aims to demonstrate empirically the influence of capital structure, company size, managerial ownership of the agency cost, and to prove empirically the influence of capital structure, company size, managerial ownership, agency cost to company performance. This research was conducted at the Indonesian Stock Exchange (BEI), which is the manufacturing company in the year 2011 to the year 2013. The company's performance is the dependent variable in this study, and agency cost as an intervening variable, while the independent variable in this study is the capital structure, the size of the company , managerial ownership. The population used in this research are manufacturing companies listed in Indonesia Stock Exchange (BEI) during 2011-2013. Sampling method by purposive sampling according to criteria that have been determined. Total sample of 131 companies. Data analysis techniques used in this research is the analysis of the path (path analisys). Results of this study indicate that: (1) capital structure statistical effect on agency cost, with a significance level of 0.002 <α 0.1. (2) The size of the company does not affect the agency cost, with a significance level of 0.242> 0.1 α. (3) managerial ownership does not affect the agency cost, with a significance level of 0.686> 0.1 α. (4) The capital structure affect the performance of the company, with a significance level of 0.086 <α 0.1. (5) The size of the company influence the performance of the company, with a significance level of 0.009 <α 0.1. (6) managerial ownership does not affect the performance of the company, with a significance level of 0.247> 0.1 α. (7) the cost Agency does not affect the performance of the company, with a significance level of 0.114> 0.1 α. Keywords: Structural modal, size companie, Managerial ownership, Agency cost and the company's performance.